2020
DOI: 10.1186/s13293-020-0282-2
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in muscle activity and motor variability in response to a non-fatiguing repetitive screwing task

Abstract: Background: Musculoskeletal disorders are more prevalent among women than among men, which may be explained by aspects of motor control, including neuromuscular requirements and motor variability. Using an exploratory approach, this study aimed to evaluate sex differences in neuromuscular responses and motor variability during a repetitive task performed on 3 days.Methods: Thirty women and 27 men performed the non-fatiguing, repetitive, 1-h screwing task. For neuromuscular responses, the mean and difference va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…Individuals with elevated SAG, both men and women, had a high probability of suffering from IFG. Poorer compliance and management in men with diabetes, along with differences in the biological response to hyperglycemia and other risk factors between the sexes [ 20 22 ], may explain these findings. Obesity is a strong predictor of an increased risk for type 2 diabetes in adults [ 23 ] and probably plays a major role in the development of diabetes [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with elevated SAG, both men and women, had a high probability of suffering from IFG. Poorer compliance and management in men with diabetes, along with differences in the biological response to hyperglycemia and other risk factors between the sexes [ 20 22 ], may explain these findings. Obesity is a strong predictor of an increased risk for type 2 diabetes in adults [ 23 ] and probably plays a major role in the development of diabetes [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two types can be distinguished. Metrics derived from linear measures, such as the standard deviation or coefficient of variation, inform of the variability magnitude (Luger et al 2020;Gaudez et al 2019;Pritchard et al 2019;Sedighi and Nussbaum 2017). They assume that variations between repetitions of a task are random and independent while these variations have deterministic properties (Caballero, Barbado and Moreno 2014).…”
Section: Practical Implication and Future Research Perspectivesmentioning
confidence: 99%
“…The individual factors, such as subjectrelated characteristics, i.e. sex, age, height or body mass index (Luger et al 2020;Gaudez et al 2019;Müller et al 2013;Madeleine, Voigt, and Mathiassen 2008;Haddad et al 2008), their work experience on the job (Sedighi and Nussbaum 2017;Madeleine et al 2003), and such as the movements they make when performing the task (Gaudez et al 2019;Gilles et al 2019) all contribute to intrinsic movement variability (Gaudez, Gilles and Savin 2016). Movement variability is inherent to human motor control.…”
Section: Introductionmentioning
confidence: 99%
“…This is believed to be a result of differences in anthropometry, strength, flexibility, and other factors of biological origin [ 19 21 ]. In addition, previous studies showed that females use different biomechanical techniques compared to males during repetitive tasks [ 19 22 ]. For instance, females demonstrated higher upper body muscle activity than males in a painting task [ 23 ].…”
Section: Introductionmentioning
confidence: 99%